DATA-BASED EDUCATION FINANCING MANAGEMENT: A STRATEGY TO IMPROVE PRIORITY INDICATOR ACHIEVEMENT IN ELEMENTARY SCHOOLS - siti munawaroh; ngurah ayu nyoman murniati; Supandi (SOSIOEDUKASI, 2026)
The low literacy and numeracy scores on the Education Report Card (Report Card) have prompted the urgency of precise financial governance. This study aims to analyze data-driven financing management strategies to improve priority indicators at SDN 5 Godong. Using a qualitative case study method, data was collected from eight informants (the Principal, Treasurer, Teachers, School Committee, and parents) through interviews, observations, and document review. Data validity was ensured through triangulation of sources and techniques. The results indicate that integrating the ARKAS (School Budget Alignment) with the Education Report Card (Report Card) increased the efficiency of instructional allocation by 15%. The findings identified the "Triple-Check Data Alignment" model as key to success, but it was hampered by the high digital administrative burden on teachers. The establishment of an internal "Data Literacy Cluster" for longitudinal analysis and diversification of funding sources is recommended to ensure the sustainability of the school quality improvement program.